1964
DOI: 10.1002/zaac.19643320313
|View full text |Cite
|
Sign up to set email alerts
|

Application of Co‐Crystallisation Technique for the production of carrier free SILVER‐111 from pile irradiated palladium

Abstract: Carrier free 111Ag has been separated from neutron irradiated palladium targets by the combined co‐crystallisation and electrodeposition techniques. Co‐crystallisation coefficient measurements of silver activity on NaCl were performed, and the best condition for the separation of Ag‐111 in more than 90% yield was carried out. The method requires no consumption of special chemicals and renders the quantitative separation and subsequent use of irradiated palladium possible. The purification of target before irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Micheev et al demonstrated that 111 Ag can be separated from neutron-irradiated palladium targets by combined co-crystallization with NaCl and electrodeposition [ 34 ]. In fact, as NaCl and AgCl are isomorphous compounds, 111 Ag + can replace a Na + ion in the crystal lattice of NaCl crystals, thus being quantitatively separated from the Pd 2+ that remains in the solution.…”
Section: Separation Of Silver Radioisotopesmentioning
confidence: 99%
See 3 more Smart Citations
“…Micheev et al demonstrated that 111 Ag can be separated from neutron-irradiated palladium targets by combined co-crystallization with NaCl and electrodeposition [ 34 ]. In fact, as NaCl and AgCl are isomorphous compounds, 111 Ag + can replace a Na + ion in the crystal lattice of NaCl crystals, thus being quantitatively separated from the Pd 2+ that remains in the solution.…”
Section: Separation Of Silver Radioisotopesmentioning
confidence: 99%
“…In the described method, the irradiated Pd target (1 mg) was treated with aqua regia (5 mL) and the obtained solution was evaporated to dryness. HCl was added and subsequently removed by evaporation [ 34 ]. The residue was dissolved in a saturated NaCl solution (50 mL) at 50 °C and the mixture was filtered with a G3 sintered glass disk.…”
Section: Separation Of Silver Radioisotopesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods for the extraction of silver-111 from neutron-irradiated palladium targets have been explored. These methods include ion exchange chromatography (Aweda et al 2013 ; Bauer et al 1997 ; Lyle and Maghzian 1968 ; Mansur et al 1995 ; Ohya et al 2020 ; Ooe et al 2019 ; Taylor 1961 ; Vimalnath et al 2007 ), alumina adsorption (Khalid et al 2000 ), liquid/liquid extraction (Alberto et al 1992 ; Lahiri et al 1997a , b ), precipitation (Blackadar et al 2022 ; Collins et al 2014 ; Haymond et al 1950 ; Sicilio et al 1956 ; Zimen 1949 ), co-crystallization (Micheev et al 1964 ) and electrodeposition (Griess and Rogers 1952 ). Nonetheless, many of these procedures involve the co-addition of macroscopic quantity of stable silver carrier or other chemical species (e.g.…”
Section: Introductionmentioning
confidence: 99%